2014
DOI: 10.1016/j.thromres.2013.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a commercially available kit to detect anti-phosphatidylserine/prothrombin antibodies in a cohort of systemic lupus erythematosus patients

Abstract: Background Antiprothrombin antibodies detection comprises two different ELISAs: prothrombin coated on irradiated plates (aPT) or phosphatidylserine/prothrombin (aPS/PT) as the antigen. While several commercial kits are available for the detection of aPT, aPS/PT are usually detected by in-house assays. Recently, a new commercially available kit was launched and, therefore, we decided to test its efficiency by comparing it to our in-house assay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 17 publications
0
23
0
Order By: Relevance
“…In such cases, a further diagnostic tool for APS with reliable performances might be crucial to guide the diagnostic process and to avoid under/over treatment (31). Finally, testing for aPS/PT by a commercial kit was proven to be a reproducible and accurate test for the detection of aPS/PT, bringing the added advantage of shorter running times when compared to in-house assays (32).…”
Section: Discussionmentioning
confidence: 99%
“…In such cases, a further diagnostic tool for APS with reliable performances might be crucial to guide the diagnostic process and to avoid under/over treatment (31). Finally, testing for aPS/PT by a commercial kit was proven to be a reproducible and accurate test for the detection of aPS/PT, bringing the added advantage of shorter running times when compared to in-house assays (32).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we analyzed the SN-APS sera for the presence of antibodies against two major cofactor proteins for aPL, prothrombin and annexin V. Our results revealed that 3 out of 24 sera from SN-APS patients (12.5%) displayed antibodies to prothrombin and 1 (4.2%) to annexin V. The datum of antiprothrombin might be underestimated, since we tested anti-prothrombin antibodies in the absence of phosphatidylserine. Indeed, anti-phosphatidylserine/prothrombin antibodies, which have been recently standardized and validated [34], seemed to represent a stronger risk factor for thrombosis than antiprothrombin [35]. However, interestingly, in SN-APS group, anti-prothrombin antibodies were detected in 3 patients, which were negative for aCL by TLC immunostaining.…”
Section: Discussionmentioning
confidence: 99%
“…Some interest has focused on the mitochondrial membrane antigen M5 which is associated with thrombocytopenia and fetal loss, and coexists with LA, aCL, anti-β2GP1, and biologically false-positive VDRL [142,143]. With the availability of a commercial anti-PS/PT assay [144], a number of reports have focused on its value [145], particularly its use in closing the seronegative gap in APS [141,146]. Although the presence of anti-PS/PT antibodies appear to be independent of the LA, they may be a potential substitute for the troubled LA assay [146,147].…”
Section: Non-criteria Autoantibodies: Phosphatidylserine/prothrombin mentioning
confidence: 99%